Optimization of Function, Maintenance and Storage of Biology Laboratory Facilities at SMA PGRI 1 Palembang: Optimalisasi Fungsi, Pemeliharaan Dan Penyimpanan Fasilitas Labolatorium Biologi Di SMA PGRI 1 Palembang - Iswandari, Vanessa R; Saputra, Ade Akhmad (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study aims to examine the role and effectiveness of biology laboratory facilities in supporting students' practical activities at SMA Negeri 1 Palembang and SMA PGRI 1 Palembang, with a focus on the implementation of laboratory functions, storage systems, and equipment maintenance procedures. The research method used is a descriptive approach with direct field observations and interviews with laboratory managers. Data collection techniques include observations of laboratory facility conditions, interviews with the laboratory head and laboratory assistants, as well as documentation of equipment maintenance and storage procedures. The collected data were then analyzed qualitatively to identify the challenges and successes in laboratory management. The results of the study show that the laboratories in both schools function well as practical tools and for developing students' scientific skills. However, there are several barriers that hinder their effectiveness, such as equipment damage and limitations in procuring new tools. At SMA PGRI 1 Palembang, the unavailability of equipment causes practical sessions to often be replaced with theory. The implications of this study indicate that the laboratory maintenance and storage system needs to be strengthened with more structured care and the procurement of new equipment. The study also recommends improving laboratory management in both schools to ensure optimal practical activities.